2015
DOI: 10.2147/ott.s82235
|View full text |Cite
|
Sign up to set email alerts
|

Anterior gradient protein 3 is associated with less aggressive tumors and better outcome of breast cancer patients

Abstract: Anterior gradient protein (AGR) 3 is a highly related homologue of pro-oncogenic AGR2 and belongs to the family of protein disulfide isomerases. Although AGR3 was found in breast, ovary, prostate, and liver cancer, it remains of yet poorly defined function in tumorigenesis. This study aimed to determine AGR3 expression in a cohort of 129 primary breast carcinomas and evaluate the clinical and prognostic significance of AGR3 in these tumors. The immunohistochemical analysis revealed the presence of AGR3 stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…49 Differential gene expression analysis of patient subgroups with good versus bad survival (based on 4 independent signatures of apoptotic proficiency) identified 11 genes similarly enriched in either of these groups, 8 of which had previously been attributed an impact on breast cancer progression or patient survival ( Figures 5 and 6). 34,[37][38][39][40][41][42][43] The expression levels of these genes also conveyed prognostic value in patients from the METABRIC dataset ( Figure 6 and Tables 1and 2), with the potential exception of CYP4X1. Of the remaining three genes, LTB failed to impact cancer-specific overall survival in the METABRIC cohort (Tables 1 and 2), while both CLIC6 and SLC7A2 were strongly associated with improved disease outcome ( Figure 6 and Tables 1 and 2), although only SLC7A2 as an independent prognostic biomarker ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…49 Differential gene expression analysis of patient subgroups with good versus bad survival (based on 4 independent signatures of apoptotic proficiency) identified 11 genes similarly enriched in either of these groups, 8 of which had previously been attributed an impact on breast cancer progression or patient survival ( Figures 5 and 6). 34,[37][38][39][40][41][42][43] The expression levels of these genes also conveyed prognostic value in patients from the METABRIC dataset ( Figure 6 and Tables 1and 2), with the potential exception of CYP4X1. Of the remaining three genes, LTB failed to impact cancer-specific overall survival in the METABRIC cohort (Tables 1 and 2), while both CLIC6 and SLC7A2 were strongly associated with improved disease outcome ( Figure 6 and Tables 1 and 2), although only SLC7A2 as an independent prognostic biomarker ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Strikingly, 7 of these 11 genes have previously been attributed an impact on breast cancer progression and patient survival that is in line with our findings. These genes are AGR3, 34 ANKRD30A, 35 BMPR1B, 36,37 STC2 38,39 and SUSD3, 40 which are all indicators of early disease or good prognosis, as well as CXCL9, 41,42 and CALML5, 43 both of which have previously been linked to disease progression or poor prognosis. Conversely, CYP4X1 (which is our hands was enriched in patients with good survival) has previously been positively correlated with tumor grade.…”
Section: Signatures Of Apoptotic Proficiency Convey Negative Prognostmentioning
confidence: 99%
“…Interestingly, Garczyk et al [ 49 ] reported that AGR3 has a prognostic impact on early detection of breast cancer, and that low- and intermediate-grade tumor patients with high AGR3 expression had an unfavorable outcome [ 49 ]. Obacz et al reported that AGR3 positivity was associated with better outcome (progression free survival and overall survival) in the subgroup of patients with tumors characterized by lower histological grade but not by higher histological grade in breast cancer [ 50 ]. Though AGR3 levels are increased in various cancers, the role of AGR3 in tumors, particularly in ovarian tumors, is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AGR3 is highly expressed in intrahepatic cholangiocarcinoma compared with its expression levels in hepatocellular carcinoma ( 15 ). In breast cancer, AGR3 is positively associated with low histological grade breast tumors ( 16 ). Recent studies have demonstrated that extracellular AGR3 can regulate breast cancer cell migration via Src signaling ( 17 ), and that AGR3 can promote the proliferative and invasive abilities of breast cancer cells, as well as chemotherapy response ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although differential expression of AGR3 has been identified among different types of cancer, including ovarian, prostate, liver and breast cancers ( 13 16 ), the role of AGR3 in breast cancer oncogenesis and development remains unclear. The present study aimed to investigate the association between AGR3 and ER status, and the function of AGR3 in ER-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%